(untitled) (Research, Society and Development, 2021)
Potato plants (Solanum tuberosum L.) have a higher requirement for phosphorus (P) to achieve high yields of tubers. In P-deficient soils, photosynthetic activity and crop productivity are considerably reduced. Thus, the aim of this study was to investigate the effects on photosynthesis and growth of potato clones cultivated at different levels of P in the soil. The experiment was conducted in a greenhouse, in a completely randomized design, using soil as substrate, where treatments were combined in a factorial scheme with three potato clones (Atlantic, SMIC 148-A and SMINIA 793101-3) and four P doses (35, 70, 140 and 280 kg P2O5 ha-1). The application of P doses changed THE PRODUCTION of dry matter of tubers and total of the clones studied. The SMIC 148-A clone presented a higher of net CO2 assimilation rate and stomatal conductance at doses of 70, 140 and 280 kg P2O5 ha-1. The Atlantic clone was the one that presented the highest total dry mass production in the lowest dose of P, as well as the clone that invested the photoassimilates more efficiently, since it obtained the highest dry mass of tubers. The highest dose of phosphorus was the one that provided the largest mass of tubers.